Masa kanak-kanak merupakan masa Faktor Keluarga Terhadap Perkembangan Anak Usia 5-6 Tahun di RA Nurul Hidayah: Faktor Keluarga Terhadap Perkembangan Anak Usia 5-6 Tahun di RA Nurul Hidayah - Fajriani, Evalina; Fitria Yulastini; Diah Ulfa Hidayati (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2023)
ntroduction Childhood is the right time to start providing stimulus so that children can develop optimally, because what children learn at the beginning of life will have an impact on life in the future. Formation of children starts from the family. The family is considered the first institution for children in providing different concepts according to their development. The role of parents is to provide guidance for their children in the formation of character and personality in each of their growth and development. Family life is an important environment for preschool children to learn survival skills and parents play an indispensable role in their growth process. In addition, every person and family has its own history or role model in raising their children. Through a good and quality parenting process, parents apply the most appropriate parenting style and best suit their children's needs. Method The research method used is an observational analytic study with a cross sectional approach Result Based on the research results, as many as (83.3%) have appropriate development, as many as (56.7%) are at the age of 6 years, as many as (60.0%) have more than one sibling, the majority of parents apply a democratic parenting style. as many (90.0%) families. Conclusion There is a relationship between family factors and the development of children aged 5-6 years at RA Nurul Hidayah